Whiteout - Clayton, Dhonielle; Jackson, Tiffany D.; Stone, Nic; Thomas, Angie; Woodfolk, Ashley; Yoon, Nicola (Quill Tree Books, an imprint of HarperCollins Publishers, 2022)
Atlanta is blanketed with snow just before Christmas, but the warmth of young love just might melt the ice in this novel of Black joy, and cozy, sparkling romance -- by the same unbeatable team of authors who wrote the New York Times bestseller Blackout! is the city grinds to a halt, twelve teens band together to help a friend pull off the most epic apology of her life. But will they be able to make it happen, in spite of the storm? No one is prepared for this whiteout. But then, we can't always prepare for the magical moments that change everything. From the bestselling, award-winning, all-star authors who brought us Blackout -- Dhonielle Clayton, Tiffany D. Jackson, Nic Stone, Angie Thomas, Ashley Woodfolk, and Nicola Yoon -- comes another novel of Black teen love, each relationship within as unique and sparkling as Southern snowflakes. -- Provided by publisher.